Edukasi pencegahan stunting di Desa Sukamaju Kecamatan Sidomulyo Lampung Selatan - Ningsih, Tri Riwayati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Stunting is a form of failure in child growth and development due to chronic malnutrition. One third of toddlers in Indonesia have below average height. The number of stunted children in Indonesia is ranked fifth in the world. To achieve the target of reducing stunting rates, changes in community behavior are needed. Purpose: The community service carried out by KKN 160 in an effort to prevent stunting is in collaboration with PKK mothers, village midwives and Sukamaju village officials. Method: The stunting prevention activities carried out in Sukamaju Village are a form of Community Service in an effort to prevent stunting. The programs implemented are in the form of education, providing PMT in the form of sweet corn, tempeh and spinach, and providing prenagen milk for pregnant women. Using interactive lecture methods, collaboration and demonstrations. Education in the form of stunting counseling with the theme